Assessment of Brain Injury Marker (Carcinoembryonic Antigen) in Preeclamptic Pregnant Women in the Third Trimester of Pregnancy - Edebiri O.E; Akpe P. E.; Adewole A.S.; Mbanaso E.L.; Ikuenobe V. E.; Ohiwerei W.O. (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Carcinoembryonic antigen (CEA) is a glycoprotein normally produced during fetal development, but presence of tissue damage and inflammation, its levels increase and this may be linked to Carcinoembryonic antigen in the pathophysiology of preeclampsia. This study aims to assess the level of Carcinoembryonic antigen (CEA) in preeclamptic pregnant women in the third trimester of pregnancy. Forty (40) consenting pregnant women were recruited from St. Philomina Catholic Hospital, Edo State, Nigeria. After the subjects were identified and recruited into the study, they were taken to the laboratory where their vital signs was taken and 10 milliliters (10 ml) of venous blood was drawn from consenting participants and placed in a lithium heparin sample bottles analyzed for Carcinoembryonic antigen (CEA) levels by fluorescence immunoassay. Data obtained from this study were analysed using Graph Pad Prism 9. Results generated were expressed as mean ± SEM and a P-value of ≤ 0.05 were considered statistically significant. The present study showed that there was statistically significant increase in the level of Brain injury marker (CEA) was observed in preeclamptic women compared to normotensive pregnant women, indicating various underlying pathophysiological processes such as Brain injury in preeclampsia.